Theoretical references that sustain the organizational climate: integrative review - Annia Lourdes Iglesias Armenteros; Julia Maricela Torres Esperón; Yuliett Mora Pérez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
The tendency to conceive of organization as the center of administrative discipline is based on what is called classical or traditional paradigm and is based on the assumption of the "company-machine" that responds to determinism, efficiency and control. This review aims to analyze updated scientific production on organizational climate. Nine articles published between 2010 and 2018 were included, framed in different administration theories for their application in organizations and evaluation of the organizational climate; The instruments used and results obtained were analyzed. The nine selected studies were written in Spanish language and all with a descriptive design. It was found that the studies describe definitions and theories which support the organizational climate. It is concluded that the theory of systems and complexity theory are present in the theoretical referents about organizational climate and gain value in the organization development. It also reaffirms the value of people for its proper functioning, as well as the importance of communication processes.